How are we doing today? An interdisciplinary debate on emotional states in contemporary society (KULT_online, 2017)
The anthology Un-Wohl-Gefühle. Eine Kulturanalyse gegenwärtiger Befindlichkeiten intervenes in the debate on the societal production of emotional (dis-)harmonies. The volume contributes to this interdisciplinary discussion by fostering the dialogue between therapeutic and cultural-theoretical positions. The collected articles explore affectivity in relation to a wide array of topics, such as sociocultural change, gender relations, psychological illness, and self-management.